2016
DOI: 10.15578/jsekp.v11i1.3170
|View full text |Cite
|
Sign up to set email alerts
|

Tingkat Kesejahteraan Nelayan Skala Kecil Dengan Pendekatan Penghidupan Berkelanjutan Di Kabupaten Indramayu

Abstract: Kabupaten Indramayu memiliki jumlah rumah tangga menengah kebawah paling banyak diProvinsi Jawa Barat. Artinya, tingkat kesejahteraan yang dimiliki masih rendah. Penelitian ini bertujuanuntuk mengkaji tingkat kesejahteraan nelayan skala kecil (≤ 5 GT) di Kabupaten Indramayu. Datayang digunakan adalah data primer dan data sekunder yang dikumpulkan dengan menggunakanteknik wawancara, observasi dan pencatatan. Analisis data menggunakan pendekatan penghidupanberkelanjutan menggunakan indikator sumber daya keuangan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 2 publications
1
11
0
12
Order By: Relevance
“…The agricultural products traded by the women (mama(s)) on the market reflected the social dynamics in the economic activities of traditional communities in Papua to maintain their family's livelihood, contributed to urban development, and achieved local cultural sovereignty. Triyanti and Firdaus (2016) have shown that these contributions to development can be made by maintaining livelihoods that strengthen the economic condition of families through education and health so as to avoid poverty and be able to achieve prosperity. Furthermore, their findings also show that the capability of access to social, natural, human, physical, and financial capital also influences sustainable family livelihoods.…”
Section: Discussion: Social Capital and Community-based Economic Systems In A Sustainable Livelihood Approachmentioning
confidence: 99%
“…The agricultural products traded by the women (mama(s)) on the market reflected the social dynamics in the economic activities of traditional communities in Papua to maintain their family's livelihood, contributed to urban development, and achieved local cultural sovereignty. Triyanti and Firdaus (2016) have shown that these contributions to development can be made by maintaining livelihoods that strengthen the economic condition of families through education and health so as to avoid poverty and be able to achieve prosperity. Furthermore, their findings also show that the capability of access to social, natural, human, physical, and financial capital also influences sustainable family livelihoods.…”
Section: Discussion: Social Capital and Community-based Economic Systems In A Sustainable Livelihood Approachmentioning
confidence: 99%
“…2016. ), serta mengaktifkan koperasi nelayan yang sudah ada ada mendirikan koperasi baru dengan sumber daya manusia pengelola yang professional (Triyanti dan Firdaus, 2016) Melalui model pembiayaan inklusif dengan system Al Mudharobah diharapkan antara para nelayan dan pemberi modal terhindar dari system riba yang di haramkan bagi umat islam seperti tercantum dalam Surat Al Baqoro ayat 276. Sebagai Lembaga keuangan yang mendukung pengembangan ekonomi yang berkelanjutan maka Bank mempunyai kewajiban untuk memenuhi kebutuhan masyarakat tersebut melalui produkproduk yang dimilikinya.…”
Section: Pendahuluanunclassified
“…Namun, kondisi lemahnya modal sosial yang dipresentasikan dalam kelembagaan rupanya tidak hanya terjadi pada nelayan di Kali Maro. Hampir di sebagian besar pesisir Indonesia, terutama nelayan kecil di Kabupaten Indramayu juga mengalami hal yang sama, indeks modal sosial termasuk kategori buruk dibandingkan indeks pembangunan sumber daya manusia dan penghidupan nelayan (Triyanti & Firdaus, 2016). Oleh karena itu, penguatan kelembagaan informal perlu dibangun dan dikembangkan di dalam kehidupan nelayan Kali Maro agar memudahkan dalam proses mobilisasi, penyebaran informasi, peningkatan kapasitas maupun menjadi representatif dalam diskusidiskusi kebijakan dan pelibatan nelayan dalam program pengembangan wilayah pesisir dan daerah aliran sungai (DAS) Kali Maro.…”
Section: Modal Sosial Sebagai Media Produksi Belajar Dan Pemasaranunclassified